Unlocking Big Data’s Potential to Strengthen Farmers’ Resilience: The Platform for Big Data in Agriculture - Jiménez, Daniel; Ramírez Villegas, Julián Armando (International Institute for Sustainable Development, 2018)
The availability of free and open access to large amounts of crop and weather data—combined with data mining approaches—enabled researchers to spot the main limiting factors of crop productivity at a site-specific scale, combine it with seasonal climate predictions, and get the information to farmers in time to inform their planting decisions. The rapid growth in processing power and global connectivity means that huge amounts of data can now be collected, shared and analyzed faster than ever before, and most importantly, can be turn into recommendations to inform the decisions of farmers and policy-makers. The increased access and use of Information and Communication Technologies (ICTs) is redefining the way in which knowledge is managed and decisions are taken. Yet many rural households in Africa, Asia, and Latin America and the Caribbean are still behind in the ICT revolution. Despite the ubiquity of technologies such as mobile phones, many farmers lack access to the kind of information they need to produce more food, more sustainably, and to respond and adapt to the impacts of climate. Most agro-climatic or food security information products are not tailored to farmers’ needs—they lack the resolution, frequency or the type of information necessary to be actionable at local levels. Harnessing the potential of Big Data, CGIAR developed the Platform for Big Data in Agriculture seeking to enable the development sector to embrace data and other digital technology approaches to solve agricultural development problems faster, better and at greater scale.